2010
DOI: 10.1021/jf101323y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Antioxidative Peptides Derived from a Thermolytic Hydrolysate of Ovotransferrin by LC-MS/MS

Abstract: Ovotransferrin is a glycoprotein well-known for its iron-binding property. Ovotransferrin was reported to have antioxidative properties, but the presence of antioxidant peptides within the protein has not been reported. The purpose of the study was to characterize the antioxidant peptides within ovotransferrin. Ovotransferrin was sonicated and hydrolyzed by thermolysin, and peptides from the hydrolysate were fractionated by ion-exchange fast protein liquid chromatography and reversed-phase high-performance liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 30 publications
(45 reference statements)
4
64
0
Order By: Relevance
“…The overall antioxidant activity of ovotransferrin was enhanced by disruption of its structure to increase the proximity of amino acid residues that scavenge free radicals and chelating pro-oxidative metals (Elias, Kellerby, & Decker, 2008). Our study showed that hydrolysis of ovotransferrin increased its antioxidant activity; 14 peptides were characterized from ovotransferrin (Shen, Chahal, Majumder, You, & Wu, 2010). Two tetrapeptides (Trp-Asn-Ile-Pro and Gly-Trp-Asn-Ile) showed the highest antioxidant activity, indicating that (Trp-Asn-Ile) might be the core motif responsible for their high antioxidant activity.…”
Section: Antioxidative Peptidesmentioning
confidence: 77%
“…The overall antioxidant activity of ovotransferrin was enhanced by disruption of its structure to increase the proximity of amino acid residues that scavenge free radicals and chelating pro-oxidative metals (Elias, Kellerby, & Decker, 2008). Our study showed that hydrolysis of ovotransferrin increased its antioxidant activity; 14 peptides were characterized from ovotransferrin (Shen, Chahal, Majumder, You, & Wu, 2010). Two tetrapeptides (Trp-Asn-Ile-Pro and Gly-Trp-Asn-Ile) showed the highest antioxidant activity, indicating that (Trp-Asn-Ile) might be the core motif responsible for their high antioxidant activity.…”
Section: Antioxidative Peptidesmentioning
confidence: 77%
“…It is unclear whether antioxidant effects of the other 19 peptides, discovered by using cell-free or chemical-based methods, have any biological significance. Shen et al [91] identified 16 antioxidant peptides from ovotransferrin guided by the oxygen radical absorbance capacity (ORAC) assay; antioxidant activity of pure peptides synthesized based on the 16 sequences was validated with the ORAC assay. Recently, Jahandideh et al [92] reported that these 16 peptides had no antioxidant activities in human umbilical vein endothelial cells.…”
Section: Current Gaps In Knowledge and Future Perspectivesmentioning
confidence: 99%
“…Various peptides derived from animal or plant proteins were reported to exhibit radical-scavenging activity in food and biological systems (Ma, Xiong, Zhai, Zhu, & Dziubla, 2010;Rao et al, 2012;Shen, Chahal, Majumder, You, & Wu, 2010;Xia, Bamdad, Gänzle, & Chen, 2012;Zhang, Mu, & Sun, 2014). One of the most widely used assays to screen anti-radical peptides is the ABTS assay.…”
Section: Introductionmentioning
confidence: 99%